Evidence on the effect of uncontrolled diabetes mellitus on orthodontic tooth movement. A systematic review with meta-analyses in pre-clinical in- vivo research. (July 2020) - Koletsi, Despina; Iliadi, Anna; Papageorgiou, Spyridon N.; Konrad, Daniel; Eliades, Theodore
Highlights: There is increasing awareness regarding orthodontic treatment in diabetic patients. Evidence form clinical studies in the field is lacking. No macroscopical effect of diabetes mellitus on tooth movement could be established. Attenuation of osteoblastic differentiation in the periodontal ligament is detected. Abstract: Objective: The aim of this review was to appraise the existing evidence from pre- clinical research on tooth movement under the condition of hyperglycemic status. Design: Electronic search was conducted in 8 databases in October 13, 2019, to identify related pre- clinical animal research with keywords being: "diabetes mellitus", "tooth movement". Eligibility criteria involved controlled animal studies, entailing tooth movement under diabetic status compared to control healthy animals. Primary endpoints involved all outcomes related to tooth movement. Risk of bias (RoB) was assessed through the SYstematic Review Centre for Laboratory animal Experimentation tool (SYRCLE), while quantitative synthesis was planned after exploration of heterogeneity, through random effects meta-analyses of standardized mean differences (SMDs) with 95 % confidence intervals (CIs). Results: Of an initial number of 290 articles retrieved, 14 papers were eligible for inclusion in the qualitative synthesis, while 9 contributed to meta-analyses. Heterogeneity of experimental conditions in individual studies was evident. The risk of bias overall was rated as unclear to high. There was no evidence of a significant effect of diabetes mellitus when tooth movement was assessed macroscopically (6 studies, SMD: 1.47; 95 % CI: -0.60, 3.53; p = 0.16). However, attenuation of osteoblastic differentiation within the periodontal ligament was detected, as there was evidence of reduction of osteopontin expression (2 studies, SMD: -3.77; 95 %CI: -4.89, -2.66; p < 0.001). Conclusions: There is currently a paucity of solid evidence with regard to alterations of the equilibrium of the implicated structures under the status of diabetes mellitus, when mechanical stimulation of teeth is attempted, with sporadic inferences from animal research. Significant research insights in how the disease impacts on orthodontic tooth movement are invaluable, at present.